2018
DOI: 10.1371/journal.pmed.1002596
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the 2014 sugar-sweetened beverage tax in Chile: An observational study in urban areas

Abstract: BackgroundIn October 2014, Chile implemented a tax modification on sugar-sweetened beverages (SSBs) called the Impuesto Adicional a las Bebidas Analcohólicas (IABA). The design of the tax was unique, increasing the tax on soft drinks above 6.25 grams of added sugar per 100 mL and decreasing the tax for those below this threshold.Methods and findingsThis study evaluates Chile’s SSB tax, which was announced in March 2014 and implemented in October 2014. We used household-level grocery-purchasing data from 2011 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
1
11

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 32 publications
3
85
1
11
Order By: Relevance
“…Current evidence supports the implementation of taxes that increase the price of products by 20 % or more to reduce the consumption of unhealthy foods (36) . The WHO already indicated this measure for sweetened beverages in 2016 (38) and several countries have considered or already adopted this measure, such as Mexico (with 10 % tax on sweetened beverages and 8 % tax on ultra-processed foods with energy density above 1151 kJ (275 kcal)/100 g) (23) and Chile (in 2014, the tax for beverages with an added sugar concentration above 6•25 g/100 ml increased from 13 to 18 %) (39) . In Brazil, several bills on the subject are under discussion in the National Congress; however, due to strong resistance from the Big Soda industry and some groups of Federal Legislators (largely financed by the Big Food and Big Soda industries), little progress has been made so far (40) .…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence supports the implementation of taxes that increase the price of products by 20 % or more to reduce the consumption of unhealthy foods (36) . The WHO already indicated this measure for sweetened beverages in 2016 (38) and several countries have considered or already adopted this measure, such as Mexico (with 10 % tax on sweetened beverages and 8 % tax on ultra-processed foods with energy density above 1151 kJ (275 kcal)/100 g) (23) and Chile (in 2014, the tax for beverages with an added sugar concentration above 6•25 g/100 ml increased from 13 to 18 %) (39) . In Brazil, several bills on the subject are under discussion in the National Congress; however, due to strong resistance from the Big Soda industry and some groups of Federal Legislators (largely financed by the Big Food and Big Soda industries), little progress has been made so far (40) .…”
Section: Discussionmentioning
confidence: 99%
“…However, a study of a 5% tax in Chile reported significantly greater declines in consumption among the highest SEP groups, 31 and a similar pattern was reported by the second Chile study. 33 The…”
Section: Meta-analyses Of Untaxed Beverage Outcomesmentioning
confidence: 99%
“…Price increases in the 3.1-3.5 percent range were found by two studies using identical data; however, one found purchases declined slightly, which seemed appropriate for this small price increase (a volume reduction of 3.4 percent in SSBs, an increase in low-taxed items of 10.7 percent, and a total calorie decrease of 4.0 percent; Caro et al 2018). A different study with the same data found the unbelievable result of a 21.6 percent decline in the volume of higher taxed SSBs purchased, with no effect on the lower tax category in Chile (Nakamura et al 2018). These two studies are indicative of the complexity of studying the impact of these complex taxes using different econometric approaches and classifying products into various tax categories.…”
Section: Fiscal Policy and Ssb Taxes: The Evidence Of Impact To Datementioning
confidence: 91%
“…Tax simulations from Chile indicate that an 18 percent tax on ultraprocessed junk foods and beverages (those high in fats, salt, sugars) is associated with the highest reduction in intake of calories, sodium, saturated fats, and added sugar, compared with alternative policies (Caro, Ng, Taillie et al 2017). Another study from Chile found a drop of 21.6 percent in the monthly purchased volume of higher-taxed sugary soft drinks (Nakamura et al 2018), but an alternate study using the same data set found, for the same 3.1 percent price increase, only a comparable 3 percent reduction in purchases (Caro et al 2018). Both studies found the same small price increase but the Nakamura one found a much larger, almost unbelievable, purchase reduction from this small price increase.…”
Section: Impact Of Diet-related Taxesmentioning
confidence: 99%